2016
DOI: 10.1016/j.jcmgh.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Characterization of Microbial Communities In Situ Within the Deeper Layers of the Ileum in Crohn’s Disease

Abstract: Background & AimsMicrobial dysbiosis and aberrant host–microbe interactions in the gut are believed to contribute to the development and progression of Crohn’s disease (CD). Microbiome studies in CD typically have focused on microbiota in feces or superficial mucosal layers of the colon because accessing DNA from deeper layers of the bowel is challenging. In this study, we analyzed the deep tissue microbiome in patients who underwent surgical resection of the small intestine.MethodsParaffin blocks were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
2
15
0
2
Order By: Relevance
“…There is strong evidence indicating that the intestinal microbiota is responsible for triggering inflammatory bowel disease (IBD): animal models of chronic intestinal inflammation are almost all mitigated when re-derived to germ-free status 1,2 ; humans with IBD have altered reactivity to their intestinal microbes 3 ; the genetic loci for human susceptibility to Crohn's disease (CD) and/or ulcerative colitis (UC) mainly encode proteins required for innate or adaptive mucosal immune defense mechanisms and overlap with genes known to cause microbiota-sensitive intestinal inflammation in animal models 4 . Whilst no persistent pathogen has been consistently identified as being responsible for IBD, strategies reducing microbiota exposure such as surgical fecal stream diversion 5 , elemental diets or antibiotic treatment can have beneficial effects in particular IBD cases [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence indicating that the intestinal microbiota is responsible for triggering inflammatory bowel disease (IBD): animal models of chronic intestinal inflammation are almost all mitigated when re-derived to germ-free status 1,2 ; humans with IBD have altered reactivity to their intestinal microbes 3 ; the genetic loci for human susceptibility to Crohn's disease (CD) and/or ulcerative colitis (UC) mainly encode proteins required for innate or adaptive mucosal immune defense mechanisms and overlap with genes known to cause microbiota-sensitive intestinal inflammation in animal models 4 . Whilst no persistent pathogen has been consistently identified as being responsible for IBD, strategies reducing microbiota exposure such as surgical fecal stream diversion 5 , elemental diets or antibiotic treatment can have beneficial effects in particular IBD cases [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that dysbiosis within deeper layers of the ileum of CD patients, there were specifically enrichment of enterotoxigenic Staphylococcus aureus . Staphylococcus (5th in the prediction list) was thus validated 36 .…”
Section: Resultsmentioning
confidence: 99%
“…We then used PathSeq as a mapping and taxonomic classification algorithm to estimate abundance of candidate microbes using read counts assigned to each organism (13). This approach has previously been used to assess mucosal dysbiosis in Crohn's disease (55). The raw data for both RNA-Seq and PathSeq are available at the Gene Expression Omnibus (accession GSE134662).…”
Section: Methodsmentioning
confidence: 99%